Modeling the Way Strategy to Improve Activities and Abilities in Performing Obligatory Prayers in Grade III Students of SD Negeri Negeri Labuy - Zubaidah; Mariamu (MANDAILING GLOBAL EDUKASIA, 2025)
This study aims to examine the effectiveness of the modeling the way strategy in enhancing the activity and competence of Grade III students at SDN Labuy in performing obligatory prayers during the 2023/2024 academic year. The research was conducted using a classroom action research approach over two cycles. Data were collected through observation, tests, and performance assessments focusing on four aspects: reading the pillars of prayer, reading the conditions of valid prayer, recognizing actions that invalidate prayer, and practicing the prayer movements. The results indicate a significant improvement in all observed aspects from Cycle I to Cycle II. The average scores increased for reading the pillars of prayer (1.1; 21.8%), reading the conditions of valid prayer (0.7; 14.8%), recognizing invalidating actions (0.7; 15.7%), and practical prayer performance (0.9; 18.3%), moving from the “good” category to the “very good” category. Additionally, the number of students achieving mastery increased from 7 students (30%) initially to 23 students (100%) by the end of Cycle II. These findings demonstrate that the modeling the way strategy is effective in improving both the learning activity and practical competence of students in performing obligatory prayers.